GAMBARAN PENDIDIKAN ORANG TUA DAN KEKERASAN PADA ANAK DALAM KELUARGA DI GAMPONG GEULANGGANG TEUNGOH KECAMATAN KOTA JUANG KABUPATEN BIREUEN - Maryam, Siti (Universitas Islam Negeri Ar-Raniry, 2017)
The violence on children in the household is often happened compared to other violence, involving the father, mother, brother, and others. In addition, the violence also arise due to economic pressures. As parents, education is the core thing in order to maintain the most important role in the family, so that the process of care for child can be avoided from violence. This study aimed to reveal the parents' education and child abuse occurring within the family in the Gampong Geulanggang Teungoh, Kecamatan Kota Juang, Kabupaten Bireuen. The results of the study indicated that the head of the family education mostly (20 people) only junior high school and 15 heads of families completed senior high school, however, there are 1 people who have never attended school at all. Parenting program including foundation class and bazaar day are the most widely followed by the head of the family. Types of violence which mostly performed were emotional abuse, economic abuse, and physical violence